Managing Growth of Clinic Livia A Skin-Care Clinic Business - Nugraha, Giovanni Sakti; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2012)
In Indonesia, demand for skin-care clinic has rose substantially along with the climb of their economic condition and citizen welfare. This happens because economic growth has major effect in increasing numbers of middle-class citizen who plays an important role as the main target of skin-care clinic business. Middle class citizen in Indonesia has grown from just 37.7% of population to 56.5% in 2010.Clinic Livia, a skin-care clinic located in Jakarta has enjoyed substantial growth within the past 5 years. Their sales has reached 2,000 patients per month and with around 100 employees on their rank shows that this business has developed significantly since first established in 1996.However other than benefits, growth can also cause problems that company should anticipate and address properly. Unfortunately, Clinic Livia still have difficulty in managing problems that was caused by their growth. To address this situation, thorough analysis is necessary to find the root-cause and subsequently build the solution.The analysis process found that main problem of Clinic Livia was identified as lack of good strategic planning. Other than that, Clinic Livia also doesn't currently have marketing division who supposed to be responsible in predicting and preparing for growth. For that purpose this paper suggests a strategic plan for Clinic Livia as a strategic foundation and proposal to create a dedicated marketing division.Keywords: marketing, skin-care clinic, small-to-medium enterprise